Water‐Lubricated Aluminum Vanadate for Enhanced Rechargeable Magnesium Ion Storage. Issue 39 (26th August 2022) - Tang, Han; Chao, Feiyang; Chen, Huibiao; Jia, Runmin; Luo, Hongyu; Xiong, Fangyu; Yao, Xuhui; Zhang, Wenwei; Zuo, Chunli; Wang, Juan; Luo, Ping; An, Qinyou
Abstract: Magnesium ion batteries (MIBs) have attracted much attention due to their low cost and high safety properties. However, the intense charge repulsion effect and sluggish diffusion dynamics of Mg 2+ ions result in unsatisfactory electrochemical performance of conventional cathode materials in MIBs. This work reports water‐lubricated aluminum vanadate (HAlVO) as high‐performance cathode material for Mg 2+ ions storage and investigates the capacity fade mechanism of water‐free aluminum vanadate (AlVO). The charge density difference based on density functional theory calculation is performed to analyze the charge transfer process of water‐lubricated/free aluminum vanadates (HAlVO/AlVO). The different charge transfer phenomena of two materials and the charge shielding effect of water molecule in HAlVO are revealed. Moreover, the single‐phase structural evolution process and the Mg 2+ ions storage mechanism of HAlVO are further investigated deeply by different in situ and ex situ characterization methods. This work proves that HAlVO is a potential candidate cathode material to satisfy the high‐performance reversible Mg 2+ ions storage, and the water‐lubricated method is an effective strategy to improve the electrochemical performance of vanadium oxides cathode. Abstract : Water‐lubricated aluminum vanadate exhibits much better magnesium ions storage performance compared with the water‐free aluminum vanadate. Based on density functional theory calculation, the charge density difference results reveal that H2 O molecules could shield the electric charge effect of magnesium ions and reduce the electrostatic interaction between magnesium ions and the oxygen atoms of vanadium oxide layer.